Предмет: Алгебра,
автор: delenainTVD
решите уравнение: x^4-2x^3-3x^2+4x+4=0
Ответы
Автор ответа:
0
Решение
x^4-2x^3-3x^2+4x+4==
(x^4-2x^3-3x^2)+4x+4=0
x² * (x² - 2x - 3) + 4*(x + 1) = 0
x² - 2x - 3x = 0
x₁ = 3
x₂ = - 1
x² - 2x - 3x = (x - 3)*(x + 1)
x² * (x - 3)*(x + 1) + 4*(x + 1) = 0
(x + 1)*(x³ - 3x² + 4) = 0
x³ - 3x² + 4 = 0
x = - 1
x³ - 3x² + 4 I x + 1
-(x³ + x²) x² - 4x + 4
-4x² + 4
-(-4x - 4x)
4x + 4
-(4x + 4)
0
x³ - 3x² + 4 = (x - 1)*( x² - 4x + 4) = (x - 1)*(x - 2)²
Ответ: x = 3; x = - 1; x = 2
x^4-2x^3-3x^2+4x+4==
(x^4-2x^3-3x^2)+4x+4=0
x² * (x² - 2x - 3) + 4*(x + 1) = 0
x² - 2x - 3x = 0
x₁ = 3
x₂ = - 1
x² - 2x - 3x = (x - 3)*(x + 1)
x² * (x - 3)*(x + 1) + 4*(x + 1) = 0
(x + 1)*(x³ - 3x² + 4) = 0
x³ - 3x² + 4 = 0
x = - 1
x³ - 3x² + 4 I x + 1
-(x³ + x²) x² - 4x + 4
-4x² + 4
-(-4x - 4x)
4x + 4
-(4x + 4)
0
x³ - 3x² + 4 = (x - 1)*( x² - 4x + 4) = (x - 1)*(x - 2)²
Ответ: x = 3; x = - 1; x = 2
Похожие вопросы
Предмет: Математика,
автор: kolya2687
Предмет: Английский язык,
автор: danilka604
Предмет: Химия,
автор: Bondarsofiya18
Предмет: Биология,
автор: salrisa